Radiocarbon Dating Informs Tree Fern Population Dynamics and Disturbance History of Temperate Forests in Southeast Australia. Issue 2 (5th November 2018) - Fedrigo, Melissa; Stewart, Stephen B; Kasel, Sabine; Levchenko, Vladimir; Trouvé, Raphael; Nitschke, Craig R
ABSTRACT: Tree ferns are slow-growing and long-lived components of temperate forests; however, these characteristics make determining size-age and population dynamics through mensuration approaches problematic while dendroecological approaches cannot be used. In this study, we use radiocarbon ( 14 C) dating of Cyathea australis and Dicksonia antarctica to (1) determine their age-to-size relationships, (2) reconstruct the age distribution of tree fern species, and (3) test if predicted ages align with the ages of the co-occurring tree community and observed disturbance history. We used the best age-size models to reconstruct the population structure of tree ferns sampled in five paired rainforest and old-growth eucalypt stands and compared these to the age structure of co-occurring tree species. The species had similar growth allometry; however, C. australis grew four times faster than D. antarctica . The age class structures of tree ferns were congruent with the associated tree species and reflected known fire history and snowfall events in the region. Tree fern abundance increased with increasing time-since-fire and post canopy disturbance. The study demonstrates that 14 C dating of tree ferns provides a means of investigating tree fern demographics and the role of disturbance in shaping their population structure in forests of southeast Australia.